Effective Stochastic Decoding Method for Electronic Medical Information Sharing (International Journal of Innovative Research in Computer Science & Technology, 2023)
Several IoT solutions have emerged as a  result of the industry's massive expansion. E-health has  the potential to provide high-quality, accessible treatment.  ' It's a challenge to keep the user 's private medical file  safe. Using a cryptography method, such as protecting  personal data, is one option. In order to communicate  information with several participants, each receiver must  have their own unique encryption key (physicians, health  agencies, etc.). Recompilation of the master password is  required by one side of the (t, n) cutoff selective encryp tion mechanism for data exchange. This study presents a  decentralized decoding method for PHR distribution that  is successful. It's simple to exchange information with  others without having to reassemble the decoding pass word. We test the chosen-ciphertext safety of our tech nique. The JPBC package is used to execute our method  on a PC. Our strategy seems to be viable and successful  in ePHR, according on the results of our tests.
Keywords: Encryption; Decryption; Internet of Things; Personal Health Records